2019
DOI: 10.32685/0120-1425/boletingeo.45.2019.484
|View full text |Cite
|
Sign up to set email alerts
|

Megacircones ediacáricos de la sienita nefelínica de San José del Guaviare y su potencial como material de referencia para datación U/Pb mediante LA-ICP-MS

Abstract: R esumen Con el objetivo de ampliar el conjunto de materiales de referencia del Laboratorio de Geocronología del Servicio Geológico Colombiano (LG-SGC) se colectaron circones provenientes de la sienita nefelínica de San José del Guaviare, localidad del Jordán (Colombia). La muestra SNG-1 se compuso de 24 circones seleccionados de la fracción situada entre 2 y 5 milímetros de largo, montados y pulidos en un bloque de resina epóxica. La datación se realizó mediante análisis de relaciones isotópicas de uranio y p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
0
7
0
3
Order By: Relevance
“…About 200km to the East of our study area, the youngest known intracratonic magmatic rocks in the NW Amazonian Craton, the Nepheline Syenite of San José del Guaviare, of Neoproterozoic-Ediacaran to Cambrian ages of ~578 Ma (Mejia et al, 2012) and biotite K/Ar and Rb/Sr cooling ages of 445 -495 Ma (Pinson et al, 1962) outcrops over > 10 square kilometers. Recently obtained own LA-ICP-MS U-Pb zircon ages of ~609 Ma in the southern extension near Jordan (Franco et al, 2018;Muñoz Rocha et al, 2019) suggest a long emplacement and cooling history for this large body. Further west, no intracratonic intrusions are reported until now.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…About 200km to the East of our study area, the youngest known intracratonic magmatic rocks in the NW Amazonian Craton, the Nepheline Syenite of San José del Guaviare, of Neoproterozoic-Ediacaran to Cambrian ages of ~578 Ma (Mejia et al, 2012) and biotite K/Ar and Rb/Sr cooling ages of 445 -495 Ma (Pinson et al, 1962) outcrops over > 10 square kilometers. Recently obtained own LA-ICP-MS U-Pb zircon ages of ~609 Ma in the southern extension near Jordan (Franco et al, 2018;Muñoz Rocha et al, 2019) suggest a long emplacement and cooling history for this large body. Further west, no intracratonic intrusions are reported until now.…”
Section: Discussionmentioning
confidence: 92%
“…The youngest known intracratonic magmatic episode in the NW Amazonian Craton is a riftrelated alkaline subsiliceous event (Nepheline Syenite of San José del Guaviare) with Neoproterozoic-Ediacaran to Cambrian ages (U-Pb zircon emplacement ages) of ~578 Ma (Mejia et al, 2012) and biotite K-Ar and Rb-Sr cooling ages of 445 -495 Ma (Pinson et al, 1962). Recent own LA-ICP-MS U-Pb zircon ages of ~ 609 Ma (Franco et al, 2018;Muñoz Rocha et al, 2019) near Jordan to the SE of the intrusion, suggest a long emplacement and cooling history for this large body that is probably associated with the Pan-African -Braziliano orogeny. Further west, no intracratonic intrusions are reported.…”
Section: Post Mesoproterozoic Eventsmentioning
confidence: 99%
“…Geochronological analyses were performed using the LA ICP-MS U-Pb zircon method in two syenite samples (Annex 3), one located in the El Capricho body (JDB-0001R) and the other located in the Cerrito body (OPP-0074R) (Figure 14). Authors such as Pinson et al (1962), Arango et al (2011Arango et al ( , 2012, Franco et al (2018), andMuñoz Rocha et al (2019) have reported ages ranging from the Ordovician to the Neoproterozoic for syenite rocks, calculated using different methods ( Ar/ 39 Ar biotite method, was reported by Arango et al (2011Arango et al ( , 2012. This age corresponds to the late Cambrian (Furongian) and was interpreted as a cooling age.…”
Section: Geochronologymentioning
confidence: 96%
“…northern SJGS bodies. Other studies, such as those of Franco et al (2018) and Muñoz Rocha et al (2019), have complemented the age records of syenite rocks and their geochemistry.…”
Section: R Esumenmentioning
confidence: 98%
See 1 more Smart Citation